Lymphoid Aggregates in the CNS of Progressive Multiple Sclerosis Patients Lack Regulatory T Cells - Bell, Luisa; Lenhart, Alexander; Rosenwald, Andreas; Monoranu, Camelia M.; Berberich-Siebelt, Friederike (Frontiers in Immunology, 2020)
In grey matter pathology of multiple sclerosis, neurodegeneration associates with a high degree of meningeal inflammatory activity. Importantly, ectopic lymphoid follicles (eLFs) were identified at the inflamed meninges of patients with progressive multiple sclerosis. Besides T lymphocytes, they comprise B cells and might elicit germinal center (GC)-like reactions. GC reactions are controlled by FOXP3+ T-follicular regulatory cells (TFR), but it is unknown if they participate in autoantibody production in eLFs. Receiving human post-mortem material, gathered from autopsies of progressive multiple sclerosis patients, indeed, distinct inflammatory infiltrates enriched with B cells could be detected in perivascular areas and deep sulci. CD35+ follicular dendritic cells, parafollicular plasma cells, and abundant expression of the homing receptor for GCs, CXCR5, on lymphocytes defined some of them as eLFs. They resembled GCs in varying extent, as few cells were positive for the key transcriptional regulator BCL-6 and ongoing proliferation, whereas a substantial number of T cells expressed high NFATc1 like GC-follicular T cells. Then again, predominant cytoplasmic NFATc1 and an enrichment with tissue-resident CD4+CD69+ cells implied a chronic state. Intriguingly, CD3+ FOXP3+ Tregs – encompassing TFRs – were completely absent. This points to less controlled humoral immune responses in eLFs possibly enabling the occurrence of CNS-specific autoantibodies in multiple sclerosis patients.